Analysis of high structural class coupling in object-oriented software systems - Savić, Miloš; Ivanović, Mirjana; Radovanović, Miloš (Computing, 2017)
Understanding coupling between classes in object-oriented (OO) software systems is useful for a variety of software development and maintenance activities. In this paper we propose a novel, network-based methodology to analyze high structural class coupling in OO software systems. The proposed methodology is based on statistically robust structural analysis of class collaboration networks whose nodes are enriched with both software metrics and domain-independent metrics used in analysis of complex networks. To demonstrate the usefulness of the methodology we analyze five open-source, large-scale software systems written in Java. Contrary to frequently reported findings, the obtained results indicate that high structural class coupling in real software systems cannot be accurately modeled by power-law distributions. Our analysis also shows that highly-coupled classes tend to be significantly more voluminous and functionally important compared to loosely coupled classes, and do not tend to be localized in class inheritance hierarchies. Finally, in four out of five analyzed systems highly coupled classes tend to have drastically higher afferent than efferent coupling. This implies that the existence of high class coupling in an OO software system would rather indicate negative aspects of extensive internal class reuse than negative aspects of extensive internal class aggregation.